2005
DOI: 10.1002/pbc.20157
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's disease in Indian children: Outcome with chemotherapy alone

Abstract: Chemotherapy alone with alternating COPP/ABVD, without additional radiotherapy, provides high rates of durable remission and is an effective therapy in childhood HD, even in case of large mediastinal mass and peripheral or abdominal bulky disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
4
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 46 publications
9
71
4
4
Order By: Relevance
“…Lymphoma and leukemia (28.33 % each) having equal incidence followed by retinoblastoma and bone tumor (11.66 %), soft tissue tumor (8.33 %) CNS tumors (5.0 %). Our results were comparable to most other Indian studies as shown in (5) , 6.15 % Bangalore Registry, 4.65 % by Mumbai Registry, 5.70 % by Delhi Registry). Similarly incidence of malignant soft tissue tumor in our study were comparable with other Indian studies as shown in Table 6.…”
Section: Introductionsupporting
confidence: 92%
“…Lymphoma and leukemia (28.33 % each) having equal incidence followed by retinoblastoma and bone tumor (11.66 %), soft tissue tumor (8.33 %) CNS tumors (5.0 %). Our results were comparable to most other Indian studies as shown in (5) , 6.15 % Bangalore Registry, 4.65 % by Mumbai Registry, 5.70 % by Delhi Registry). Similarly incidence of malignant soft tissue tumor in our study were comparable with other Indian studies as shown in Table 6.…”
Section: Introductionsupporting
confidence: 92%
“…In some studies, chemotherapy alone was used as the initial treatment [3,12,24]. In a study by Ertem et al [3] every patient received chemotherapy for the initial treatment, including the COPP, ABVD, and ABVD regimens alternating with COPP, to be given as a total of 12 courses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in our country and most of the developing parts of the World lymphomas just follow the leukemias in frequency [32] . With advanced diagnostic and therapeutic facilities the survival rates in low and high risk patients with HL increased to 95% and 90% respectively [33,34] . Similarly, improved results after HL treatment were also published in articles from Turkey in recent years [35,36] .…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…The mostly used chemotherapeutic regimens in HL are mechlorethamine, vincristine, prednisone and procarbazine (MOPP), cyclophosphamide, vincristine, prednisone and procarbazine (COPP), doxorubicin, bleomycin, vinblastine, dacarbazine (DBVD), OPPA (vincristine, procarbazine, prednisone, adriamycin), and MOPP/DBVD alternating protocols [33,34] . Among the acute side effects of multiagent chemotherapy protocols nausea and vomiting are the leading ones.…”
Section: Treatment Toxicity In Hlmentioning
confidence: 99%
See 1 more Smart Citation